Analysis of NOAA-Generated Tropospheric Refraction Corrections for the Next Generation Nationwide DGPS Service - Dodd, David; Bisnath, Sunil (The International Hydrographic Review, 2006)
The U.S. Coast Guard has begun the modernization of its Nationwide Differential GPS (NDGPS) beacon network. One potential component of modernization is to provide the information necessary for long baseline, centimetrelevel, differential carrier phase processing. In order to achieve these results, improved handling of atmospheric refraction of the incoming GPS signals must be achieved. The utility of the NOAA tropospheric delays in position determination was accomplished by supplying the NOAA zenith delay estimates to an in-house ionospheric-free relative GPS processor. Results indicate that the most significant improvement is observed in upcomponent bias reduction of a few centimeters to more than four decimeters.